Pemertahanan Bahasa dan Budaya pada Masyarakat di Era Literasi Digital - Arinah Fransori; Nur Irwansyah; Friza Youlinda Parwis (Journal on Education, 2023)
Language and culture are interrelated, with society. In today's modern era, how the development of language and culture share and go hand in hand, keep pace with technological advances and the development of knowledge. In millennial or urban societies, language and culture are more eroded by the times. Then how is the language and culture preservation. The purpose of this study is to see how the form of language and cultural preservation of the community in the form of traditional children's games, development, are there any children who know the game! In the current era of the current digital generation. The theory used in this research is language and culture theory. The subjects of this study were children and parents in Depok Village, West Java. This research method is a qualitative descriptive study with a descriptive analytical approach. The data techniques used were interviews, observation. The results of this study are the forms of the existence (forms) of language and cultural preservation in traditional children's games in today's digital literacy era.